Pembelajaran Menulis Karya Ilmiah Berbasis Pendekatan Pembelajaran Kontekstual: Penelitian - Febrianca Toloy; Sayama Malabar; Salam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the learning achievement of writing scientific papers with current social problems before and after the use of contextual learning approaches and the influence of this approach. The design and research used pre-experimental by impelementing one class pretest-posttest. The method in sampling is purposive sampling the technique in analyzing data using descriptive statistical techniques hyphothesis testing applies the results of the t-test. The results and this study prove that the average value before using the contextual learning approach is 30,4. Then the results and t-test state that the contextual learning approach has a very significant influence on the learning achievement of writing scientific papers with current social problems with a sig value (2-tailed) of 0,005. The conclusion is that Ho is rejected and Ha is accepted.